Effect of PEG on phase, morphology and photocatalytic activity of CeVO4nanostructures - Anukorn Phuruangrat (2018)
© 2016 Elsevier B.V. All rights reserved. CeVO4nanostructures were successfully synthesized by polyethylene glycol-assisted hydrothermal process. The products synthesized in the solutions containing 0.000-0.020 g polyethylene glycol (PEG) were characterized by X-ray diffraction (XRD) and transmission electron microscopy (TEM). For the use of 0.015 and 0.020 g PEG, the products were uniform and pure tetragonal CeVO4nanorods growing along the [001] direction. The stretching and bending modes of VO43- tetrahedrons were detected by Fourier transform infrared (FTIR) and Raman spectroscopy. Methylene blue was used as a representative dye pollutant for evaluating photocatalytic activity under UV radiation. In this research, CeVO4nanorods synthesized in the solution containing 0.015 g PEG showed the highest photodegradation of 98.03% and the highest apparent rate constant of 0.0128 min-1within 300 min.